On the Myanmar amber field-crickets described as “transitional” mole crickets (Orthoptera: Gryllidea) - Cadena-Castañeda, Oscar J.; Tavares, Gustavo Costa; Hu, Tian-Hao; He, Zhu-Qing (Zootaxa, 2024)
Two recent contributions on amber crickets from Myanmar are analyzed and contrasted. The first contribution was published by Cadena-Castañeda et al. (2023), and the second by Gu et al. (2024). The positions of both contributions are compared, and the different results are discussed in terms of morphology, phylogeny, and taxonomy. The following nomenclatural acts are proposed: at the suprageneric level, the family †Pseudogryllotalpidae Gu, Yuan & Ma, 2024 syn. nov. is synonymized under the subtribe †Pherodactylina Cadena-Castañeda & He, 2023 (Sclerogryllini), maintaining its placement in the family Gryllidae. At the genus level, †Pseudogryllotalpa Gu, Yuan & Ma, 2024 syn. nov., †Unidigitus Gu, Yuan & Yue, 2024 syn. nov., and †Petilus Gu, Yuan & Ma, 2024 syn. nov. are synonymized under †Pherodactylus Poinar, Su & Brown, 2020. Similarly, the synonymy of †Tresdigitus Xu, Fang & Wang, 2020 with †Pherodactylus is confirmed. †Chunxiania Xu, Wang & Fang, 2022 is revalidated, now including only one species †Chunxiania fania Xu, Wang & Fang, 2022. At the species level, †Pseudogryllotalpa scalprata Gu, Yuan & Ma, 2024 syn. nov., †Petilus zhengi Gu, Yuan & Ma, 2024 syn. nov., and †Unidigitus longialatus Gu, Yuan & Yue, 2024 syn. nov. are considered synonyms of †Pherodactylus micromorphus Poinar, Su & Brown, 2020, while †Chunxiania fascia Gu, Yuan & Ma, 2024 syn. nov. is synonymized under †Chunxiania fania Xu, Wang & Fang, 2022. Additionally, the synonymy of †Tresdigitus gracilis Jiang, Xu, Jarzembowski & Xiao, 2022 under †Pherodactylus rectanguli (Xu, Fang & Wang, 2020) is corroborated. These synonymies were thoroughly justified, reducing the number of species from eight to three and genera from six to two. The other taxa represent different sexes or developmental stages of the three recognized species. The studied taxa are considered field crickets with notable adaptations to subterranean life compared to other Gryllidae, refuting their classification as an independent family related to Gryllotalpoidea.